(untitled) (Nigerian Journal of Technology, 2018)
A process that utilized CO2 recovered from thermal power plant flue gas for methanol production was simulated using Aspen HYSYS V8.4 software. Exergy and economic analyses approaches were used to determine the optimum number of trays in the distillation column for economic operation of the process. The results from both approaches showed that the optimum numbers of trays were 20 and further increase in the number of trays did not yield any significant improvement in the process efficiency and quality of methanol produced. The profitability analysis of the plant showed a payback period of 3 years. The study concluded that locating such plant close to the thermal power plant will mitigate the emission of CO2 by providing onsite utilization for the CO2 emitted and captured from the thermal power plant. http://dx.doi.org/10.4314/njt.v37i2.11